2016
DOI: 10.1208/s12248-016-9897-y
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Chitosan and Sericin from the Microspheres-Embedded Wound Dressing for the Prolonged Anti-microbial and Wound Healing Efficacy

Abstract: One approach in wound dressing development is to incorporate active molecules or drugs in the dressing. In order to reduce the frequency of dressing changes as well as to prolong wound healing efficacy, wound dressings that can sustain the release of the active molecules should be developed. In our previous work, we developed chitosan/sericin (CH/SS) microspheres that released sericin in a controlled rate. However, the difficulty of applying the microspheres that easily diffuse and quickly degrade onto the wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Alginate hydrogels are applied in wound healing treatments through the construction of wound dressings [12][13][14][15]. Several studies showed that the bioavailability of drugs encapsulated in alginate hydrogels is greater than that of the free drug applied directly at the lesion site, thus increasing the efficacy of healing.…”
Section: Chemistry and Physicochemical Properties Of Alginatementioning
confidence: 99%
“…Alginate hydrogels are applied in wound healing treatments through the construction of wound dressings [12][13][14][15]. Several studies showed that the bioavailability of drugs encapsulated in alginate hydrogels is greater than that of the free drug applied directly at the lesion site, thus increasing the efficacy of healing.…”
Section: Chemistry and Physicochemical Properties Of Alginatementioning
confidence: 99%
“…In the drug delivery field, SS has been employed, among other proteins, in the formulation of drug delivery systems in the form of both micro [18,19] and nanoparticles [14,20]. Protein-based nano-systems are being used to improve the cellular uptake and the body's distribution of the drug, as well as to replace materials that are not biocompatible or have a negative impact on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the slow release of antimicrobial agent from wound dressing has the advantage of treating infected wounds in a mild way (Gomes et al, 2015). So, nanoparticles impregnated into fibers offer great opportunities for improving wounds treatments due to the easier applicability and more uniform dispersion over the wound surface (Aramwit et al, 2016;Romano et al, 2015).…”
Section: Introductionmentioning
confidence: 99%